Courageous vulnerability : ethics and knowledge in Proust, Bergson, Marcel, and James - Slegers, Rosa (Studies in contemporary phenomenology ;, 2010)
This work develops the ethical attitude of courageous vulnerability through the integration of the phenomenon of involuntary memory in Marcel Proust's work and a variety of closely related themes taken from the philosophies of Henri Bergson, William James, and Gabriel Marcel.